P559 Efficacy of Ustekinumab in the treatment of patients with Crohn's disease with failure to previous conventional or biologic therapy: an observational real-life study. (27th May 2021) - Miranda, A; Cuomo, A; Camera, S; Ciacci, C; De Filippo, F R; Gravina, A G; D'Onofrio, V; Melina, R; Manguso, F; Priadko, K; Facchiano, A; Bennato, R; et al.
Abstract: Background: Ustekinumab (UST), a human anti-IL12/23p40 monoclonal antibody, was approved by FDA and EMA for the treatment of moderate to severe Crohn's disease (CD). Whether UST is effective in inducing deep remission, including mucosal healing and transmural healing, in patients with CD in a real life setting is not completely clear. Methods: The study was performed on 92 subjects (47 males; 45 females; mean age: 42 (17–78) from six medical centers in Campania, Italy, with confirmed diagnosis of moderate to severe Crohn's disease and no neoplasia. In all patients diagnosis of CD had been reached to years earlier. Before inclusion, all patients had been exposed and had failed to respond to conventional and/or at least one biological therapy.The administration of UST was as follows: IV infusion at week 0 (3 vials of 130 mg each if body weight of 55–85 kg; 2 vials of130 mg each if body weight < 55 kg) and subsequent SC injections (90 mg) q8w thereafter. At enrollment, all subjects underwent colonoscopy and were divided into groups according to endoscopic evaluation: 5 (5.4%) patients had erosions; 24 (26.1%) inflammation; 63 (68.5%) ulcers. Based on the CDAI value, 52 (56.5%) patients had a CDAI of 180–220, 35 (38%) had a CDAI of 220–450, and 5 (5.4%) had a CDAI >450. All patients underwent endoscopic examination and bowel MRI or ultrasonography at baseline and at week 52 to evaluate mucosal and transmural healing. Clinical response was defined as a reduction of CDAI by at least 100 points; clinical remission when CDAI was lower than 150. Clinical response and remission were evaluated at baseline and on 5 different occasions throughout a 12 months follow-up. Incidence of treatment-related adverse events (TRAEs) was recorded during the study period. Results: Seventeen patients interrupted therapy while 75 patients continued follow-up until the fifth visit. Clinical response at week 52 was achieved in 38 (50, 5%) patients and clinical remission in 29 (39%). Twenty-six (34%) patients showed mucosal healing, 34 (45%) showed partial endoscopic response. Fifteen patients (20%) did not show any change during endoscopic evaluation at follow-up. All patients showing mucosal healing also showed transmural healing, as assessed by ultrasonography or MRI. No major TRAEs were observed during treatment. Conclusion: In this multi-center, real life study, we show that UST was well tolerated and effective in inducing clinical response and clinical remission in patients with moderate to severe CD who had previously failed to respond to conventional or biologic therapy. UST showed limited efficacy in inducing deep remission (i.e. mucosal+transmural healing).